1984
DOI: 10.1021/np50034a005
|View full text |Cite
|
Sign up to set email alerts
|

Neoisostegane, a New Bisbenzocyclooctadiene Lignan Lactone from Steganotaenia araliacea

Abstract: Neoisostegane, the first naturally occurring steganin without a functional group at C-5, was isolated from two different collections of Steganotaenia araliacea. The structure of neoisostegane, which contained five aromatic methoxyl groups rather than the more usual three methoxyls and one methylenedioxy moiety, was elucidated by comparison of the pmr coupling constants with those of synthetic steganes and by selective decoupling experiments. The structure was confirmed by cmr data, by preparation of a derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 10 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…Achiwa and co-workers developed a catalytic enantioselective hydrogenation of a-arylidenesuccinic acid half ester 140 en route to the stereoselective total syntheses of three naturally occurring lignans: (þ)-collinusin, (À)-deoxypodophyllotoxin, 226 and (þ)-neoisostegane (Scheme 29.9). 226,227 The enantioselective hydrogenations of 140 were carried out at 30 C for 40 hours in methanol in the presence of Et 3 N under 1 atm of hydrogen using 0.2 mol% of a neutral Rh(I)-complex as a precatalyst, which was prepared in situ from (S,S)-MOD-DIOP and 1/2[Rh(COD)Cl] 2 in methanol. 228 After the workup, hydrogenation product (R)-141 was obtained in almost quantitative yields and enantioselectivity (up to 93-95% ee).…”
Section: Rhodium-catalyzed Stereoselective Hydrogenation Of Functionamentioning
confidence: 99%
“…Achiwa and co-workers developed a catalytic enantioselective hydrogenation of a-arylidenesuccinic acid half ester 140 en route to the stereoselective total syntheses of three naturally occurring lignans: (þ)-collinusin, (À)-deoxypodophyllotoxin, 226 and (þ)-neoisostegane (Scheme 29.9). 226,227 The enantioselective hydrogenations of 140 were carried out at 30 C for 40 hours in methanol in the presence of Et 3 N under 1 atm of hydrogen using 0.2 mol% of a neutral Rh(I)-complex as a precatalyst, which was prepared in situ from (S,S)-MOD-DIOP and 1/2[Rh(COD)Cl] 2 in methanol. 228 After the workup, hydrogenation product (R)-141 was obtained in almost quantitative yields and enantioselectivity (up to 93-95% ee).…”
Section: Rhodium-catalyzed Stereoselective Hydrogenation Of Functionamentioning
confidence: 99%
“…Both compounds were found in the extracts of steganotaenia araliacea 26,27 but interestingly possess the opposite axial chirality. 26,28 Most probably the substitution in C5 position (see Figure 2, structures 3 and 4) defines the different alignment for the cyclization step in case of steganacine's biosynthesis. Another lignan natural product is (-)--conidendrin (8).…”
Section: Introductionmentioning
confidence: 99%
“…In 1973 Kupchan et al reported the presence of antileukemic lignan lactones in Steganotaenia araliacea of Ethiopian origin [5]. Over the next 20 years there was extensive activity to investigate the structure of related lignans and saponins, mostly in those from Steganotaenia araliacea of West African origin [6]- [15]. In addition, these structural studies stimulated a flurry of synthetic chemistry [16]- [19].…”
Section: Introductionmentioning
confidence: 99%